A translucent mirror : history and identity in Qing imperial ideology - Crossley, Pamela Kyle. (Berkeley : University of California Press, 1999)
This volume presents an exploration of the origins of nationalism and cultural identity in China, tracing the ways in which a large, early modern empire of Eurasia, the Qing incorporated neighbouring, but disparate, political traditions into a new style of emperorship.
"In this exploration of the origins of nationalism and concepts of racial identity in China, Pamela Kyle Crossley traces the shifting ideologies of a large, early modern land-based empire, the Qing (1636-1912). Drawing on a wide variety of primary sources, Crossley argues that motifs introduced under the Qing in the eighteenth century - part of the crystallizing categories of identity that the Qing themselves promoted - continue to distort the modern understanding of Qing origins. What has often been repudiated by nationalist foes of empire, it turns out, is frequently itself a creation of empire."--Jacket
Ideology, rulership, and history -- Conquest and the blessing of the past -- Imperial universalism and circumscription of identity -- The Great Wall -- Trial by identity -- A discourse on ancestry -- Political names in Nurgan -- The Liaodongese -- The character of loyalty -- The early Nikan spectrum -- Conquest and distinctions -- Personifications of fidelity -- The father's house -- Boundaries of rule -- Origins of the khanship -- The collegial impulse -- The reinvention of treason -- Empire and identity -- Subjugation and equality -- Generating imperial authority -- Authenticity -- Surpassing limits -- The celestial pillar -- The wheel-turning king -- The center -- Debating the past -- The power of speech -- The universal prospect -- The banner elites -- Shady pasts -- Manchuness -- Following Chinggis -- The empty constituency -- Postscript: race and revolution at the end of the empire.
"The Philip E. Lilienthal Asian studies imprint."
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: China -- Politics and government -- 1644-1912.; Nationalism -- China; Nationalisme -- Chine; Chine -- Politique et gouvernement -- 1644-1912.; HISTORY; Nationalism; Politics and government; China; Vorstenhuizen; Geschiedenis; Identiteit; Imperialisme; Ideologie; China; 1644-1912